Short-Term Cardiovascular Response to Short-Radius Centrifugation With and Without Ergometer Exercise - Diaz-Artiles, Ana; Heldt, Thomas; Young, Laurence R. (Frontiers in Physiology, 2018)
Artificial gravity (AG) has often been proposed as an integrated multi-system countermeasure to physiological deconditioning associated with extended exposure to reduced gravity levels, particularly if combined with exercise. Twelve subjects underwent short-radius centrifugation along with bicycle ergometry to quantify the short-term cardiovascular response to AG and exercise across three AG levels (0G or no rotation, 1G, and 1.4G; referenced to the subject’s feet and measured in the centripetal direction) and three exercise intensities (25W, 50W, and 100W). Continuous cardiovascular measurements were collected during the centrifugation sessions using a non-invasive monitoring system. The cardiovascular responses were more prominent at higher levels of AG and exercise intensity. In particular, cardiac output, stroke volume, pulse pressure, and heart rate significantly increased with both AG level (in most of exercise group combinations, showing averaged increments across exercise conditions of 1.4 L/min/g, 7.6 mL/g, 5.22 mmHg/g, and 2.0 bpm/g, respectively), and workload intensity (averaged increments across AG conditions of 0.09 L/min/W, 0.17 mL/W, 0.22 mmHg/W, and 0.74 bpm/W respectively). These results suggest that the addition of artificial gravity to exercise can provide a greater cardiovascular benefit than exercise alone. Hierarchical regression models were fitted to the experimental data to determine dose-response curves of all cardiovascular variables as a function of AG-level or exercise intensity during short-radius centrifugation. These results can inform future studies, decisions, and trade-offs towards potential implementation of AG as a space countermeasure.